Reduced glyoxalase 1 activity in carotid artery plaques of nondiabetic patients with increased hemoglobin A1c level - Peters, Andreas; Lercher, Marieluise; Fleming, Thomas; Nawroth, Peter Paul; Bischoff, Moritz; Dihlmann, Susanne; Böckler, Dittmar; Hakimi, Maani (Journal of vascular surgery, 2016)
OBJECTIVE: Glyoxalase 1 (GLO1) is ubiquitously expressed in the cytosol of the cell and is the major opponent against the reactive metabolite methylglyoxal, which is involved in the development of atherosclerosis. Nondiabetic individuals with an increased hemoglobin A1c (HbA1c) level are at higher risk for development of cardiovascular diseases. As such, this study investigated whether there was an association between reduced GLO1 activity in atherosclerotic lesions of nondiabetic patients with an increased HbA1c level. - METHODS: HbA1c level was determined in venous blood of patients with carotid artery disease. Protein level of GLO1 was measured in endarterectomy-derived carotid artery plaques by Western blotting. Activity was measured by spectrophotometric assay in the plaques as well as in the erythrocytes; GLO1 activity in erythrocytes was compared with that in a cohort of healthy individuals (n = 15; 33% men; average age, 60 years). - RESULTS: There were 36 patients with carotid artery disease (69% men; average age, 69 years) included in this study and divided into two equal groups: group I, HbA1c < 5.7% (<39 mmol/mol); and group II, 5.7% ≤ HbA1c < 6.5% (39 mmol/mol ≤ HbA1c < 48 mmol/mol). GLO1 activity in carotid plaques was reduced by 29% in group II compared with group I (P = .048), whereas protein expression was unchanged (P = .25). Analysis of GLO1 activity in erythrocytes revealed no difference between the groups (P = .36) or in comparison to healthy controls (P = .15). Examination of clinical parameters showed an increased amount of patients with concomitant peripheral arterial disease in group II (44% vs 10%; P = .020). - CONCLUSIONS: Reduction of GLO1 activity in atherosclerotic lesions of nondiabetic patients with increased HbA1c is associated with a functional involvement of this protective enzyme in atherogenesis. Systemic GLO1 activity seems to be independent of both HbA1c and localized atherosclerosis as it was unchanged between group I and group II as well as compared with healthy controls, respectively.
Gesehen am 12.10.2020